Music therapy, cognition and communication: creative improvisation in a single case of a child with unspecified intellectual developmental disorder - González Granero, María Belén (MISOSTENIDO, 2021)
Musical improvisation is addressed in different types of disciplines and one of them is music therapy, where under certain conditions it has been seen to have positive effect on the improvement of cognitive functions and communication. The aim of this project was to use creative improvisation with a six-year-old boy with an unspecified neurodevelopment disorder for three months for the improvement of cognitive functions and communication. The sessions are divided into two parts; a rhythmic part to work on attention and concentration with premeditated and improvised rhythms and a melodic part in which communication is worked on through words known to the child to create a musical dialogue between the music therapist and the patient. After the data analysis, it was observed that after eleven sessions of rhythmic-musical work through creative improvisation, the data obtained were positive, having achieved all the objetives proposed for the project.
Musicoterapia, cognición y comunicación: Improvisación creativa en un único caso de un niño con trastorno del desarrollo intelectual no especificado
La improvisación musical se aborda en diferentes tipos de disciplinas y una de ellas es la Musicoterapia, en la que bajo determinadas condiciones se ha visto que tiene un efecto positivo en la mejora de las funciones cognitivas y la comunicación. El objetivo de este proyecto fue usar la improvisación creativa con un niño de seis años con un trastorno del desarrollo intelectual no especificado durante tres meses para la mejora de las funciones cognitivas y la comunicación. Las sesiones se dividieron en dos partes; una rítmica para trabajar la atención y la concentración con ritmos premeditados e improvisados y otra parte melódica en la que se trabaja la comunicación a través de palabras conocidas para el niño para poder llegar a crear un diálogo musical entre el músicoterapeuta y el paciente. Tras el análisis de datos, se observó que, tras once sesiones de trabajo rítmico-musical a través de la improvisación creativa, los datos obtenidos fueron positivos, habiendo conseguido todos los objetivos propuestos para el proyecto.
Keywords: music therapy; neurodevelopment disorder; creative music therapy; improvisation; cognition; musicoterapia; trastorno del desarrollo intelectual; musicoterapia creativa; improvisación; cognición; MISOSTENIDO